Contribution à l’étude des sillons subverticaux intéressant des facettes interproximales - Philippe Poisson; Bruno Maureille; Chistine Couture; Jean-François Tournepiche; Jean-Louis Miquel (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Neanderthal dental remains were discovered in the cave at Rochelot (Charente, France) which is known to have been inhabited by hyenas. Two left teeth, PM1 and PM2, presented subvertical grooves located on their antagonist interproximal facets. Macroscopic and microscopic examination revealed that each vertical groove of an interproximal facet resembled its antagonist groove. Bibliographical research and our experiments on modern teeth have led us to develop a chonological classification of the elements leading to the ante mortem formation of these subvertical grooves.